Canopy Target Dimensions For Infrared Thermometry - O'Toole, J.C.; Real, J. (Wiley, 1984)
The increasing use of infrared thermometry in agricultural research and management obviates the necessity of users being cognizant of the instrument's target area characteristics. In this note, we illustrate the target dimensions when an infrared thermometer of specified field of view (4°, 8°, and 20°) is used to remotely sense surface temperature of a leaf, canopy, or crop surface. Knowledge of target dimensions and special characteristics related to the ellipse center and target point at various distances to and angles above the target surface should decrease error in surface temperature measurements and assist in standardization of techniques.